Comparing the Prognostic Value of PTEN and Akt Expression with the Mitotic Activity Index in Adjuvant Chemotherapy-Treated Node-Negative Breast Cancer patients aged <55 years - Emiel A. M. Janssen; Håvard Søiland; Ivar Skaland; Einar Gudlaugson; Kjell H. Kjellevold; Arne Nysted; Jon-Arne Søreide; Jan P. A. Baak (Cellular Oncology)
Background: The prognostic value of the PI3K/Akt/mTOR pathway and PTEN in invasive breast cancer (IBC) is controversial. Cell proliferation, especially the Mitotic Activity Index (MAI), is strongly prognostic in lymph node-negative (LNneg) invasive breast cancer. However, its prognostic value has not been compared with the value of Akt and PTEN expression. Material and Methods: Prognostic comparison of Her2Neu, p110alpha (PIK3CA), Akt, mTOR, PTEN, MAI and cell-cycle regulators in 125 LNneg patients aged <55 years with cyclophosphamide, methotrexate, and 5-fluorouracil (CMF)-based adjuvant systemic chemotherapy. Results: Twenty-one (17%) patients developed distant metastases = DMs (median follow-up: 134 months). p110alpha correlated (p = 0.01) with pAkt but only in PTEN-negatives; pAkt correlated (p = 0.02) with mTOR. PTEN-negativity correlated with high MAI, high grade and ER-negativity (p = 0.009). The MAI was the strongest prognosticator (Hazard Ratio = HR = 2.9, p = 0.01). Her2Neu/p110α/Akt/mTOR features have no additional prognostic value to the MAI. PTEN had additional value but only in MAI < 3 (39/125 = 31%; 8% DMs). 19/39 = 49% of the MAI < 3 patients have combined MAI < 3 / PTEN+ with 0% DMs, contrasting 15% DMs in MAI < 3 / PTEN− (p = 0.03). Conclusions: In T1−3N0M0 adjuvant CMF-treated breast cancer patients aged <55 years, MAI was the strongest survival predictor. The PI3K/Akt/mTOR pathway and cell-cycle regulator characteristics had no additional prognostic value, but PTEN has. Patients with combined MAI < 3 & PTEN-positivity had 100% survival. The small subgroup of MAI < 3 patients that died were PTEN-negative.